1991
DOI: 10.1073/pnas.88.13.5533
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for mouse hepatitis virus is a member of the carcinoembryonic antigen family of glycoproteins.

Abstract: The BALB/c (6,7). Resistance of SJL/J mice to MHV infection is a recessive trait mapped to the Hv-2 locus on mouse chromosome 7 (8, 9). Membranes from intestine and liver of SJL/J mice do not bind MHV or anti-receptor mAb CC1, suggesting that resistance to infection is due to absence of a functional virus receptor (3, 4). SJL/J mice express a 100-to 110-kDa glycoprotein antigenically related to the MHV receptor. Because this SJL/J receptor homolog binds neither MHV-A59 virus nor anti-receptor mAb CC1, we post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
343
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(350 citation statements)
references
References 39 publications
6
343
0
Order By: Relevance
“…A l l0K receptor protein has been isolated from the brush border membrane of hepatocytes and enterocytes (Williams et al, 1990) and was shown to belong to the carcinoembryonic antigen family of glycoproteins (Williams et al, 1991). In the case of MHV it is not known whether Neu5,9Ac2 is involved in virus binding or infection of cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A l l0K receptor protein has been isolated from the brush border membrane of hepatocytes and enterocytes (Williams et al, 1990) and was shown to belong to the carcinoembryonic antigen family of glycoproteins (Williams et al, 1991). In the case of MHV it is not known whether Neu5,9Ac2 is involved in virus binding or infection of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Strain MHV-A59 has been shown to bind to a 100K to 110K protein present in membranes from hepatocytes and enterocytes of susceptible mice, but absent in comparable preparations from resistant mice (Boyle et al, 1987). A monoclonal anti-receptor antibody that prevents MHV from infecting susceptible mouse cells was used for affinity purification of the receptor (Williams et al, 1990), which has been shown to be a member of the carcinoembryonic antigen family of glycoproteins (Williams et al, 1991). It is not known whether a related receptor is required for other coronaviruses to initiate infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although speculative, the function of VCBPs might be to recognize determinants on various pathogens. There is considerable precedent for IgSF-related viral receptors, including those for poliovirus (poliovirus receptor) 116 , reovirus (junctional adhesion molecule, JAM) 117 , HIV (CD4) 118 , mouse hepatitis virus (CEA-related cell-adhesion molecule 1, CEACAM1) 119 , measles virus (signalling lymphocytic activation molecule, SLAM) 120 and others. Other potential functions for VCBPs include binding to fungal or bacterial surfaces, direct opsonization, and self-and non-self-recognition 3,7 .…”
Section: Vcbps In Protochordatesmentioning
confidence: 99%
“…Kim et al, 1991;H. Wang et al, 1991Williams et al, 1991Brown et al, 1993Hofer et al, 1994 envelope with the limiting cellular membrane (Fig. 1).…”
mentioning
confidence: 99%